2001
DOI: 10.1302/0301-620x.83b7.0831023
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of isolated injuries of the lunotriquetral ligament

Abstract: We studied 57 patients with isolated lunotriquetral injuries treated by arthrodesis, direct ligament repair, or ligament reconstruction. The outcomes were compared by using written questionnaires, the Disabilities of the Arm, Shoulder and Hand (DASH) score, range of movement, strength, morbidity and rates of reoperation. Isolated lunotriquetral injury was confirmed by arthroscopy or arthrotomy. The mean age of the patients was 30.7 years (15.4 to 53.7) and the injuries were subacute or chronic in 98.2%. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 13 publications
0
10
0
3
Order By: Relevance
“…103 Shin et al demonstrated that 80% of patients who had open repair were satisfied with the outcome and the rate of complication was 40%. 105 LTL reconstruction is a procedure indicated more often than open repair. Recently, two procedures have been mainly applied: extrinsic tenodesis and dorsal capsular reinforcement.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…103 Shin et al demonstrated that 80% of patients who had open repair were satisfied with the outcome and the rate of complication was 40%. 105 LTL reconstruction is a procedure indicated more often than open repair. Recently, two procedures have been mainly applied: extrinsic tenodesis and dorsal capsular reinforcement.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…106 Shin et al found that although complications and reoperation rates Figure 18 The technique of reconstruction of the lunotriquetral ligament with a distally based strip of the tendon of extensor carpi ulnaris. From Shin et al, 105 with permission. Figure 19 Illustration of the reticular flap technique.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The aim of repair is to restore carpal kinematics. Although Ritt et al 13 showed in cadavers that ligament repair does not reproduce normal carpal kinematics, clinical results 2,28 suggest that the procedure effectively relieves symptoms. Primary ligament repair is less efficacious when performed after the acute inflammatory response or when performed in patients demanding high use.…”
Section: Arthroscopymentioning
confidence: 99%
“…Primary ligament repair is less efficacious when performed after the acute inflammatory response or when performed in patients demanding high use. 28 In patients with chronic injuries, ligament reconstruction should be weighed against lunotriquetral fusion. Reconstruction is performed by using the radial half of the extensor carpi ulnaris tendon, leaving its distal attachment intact.…”
Section: Arthroscopymentioning
confidence: 99%
See 1 more Smart Citation